Share repurchases, catering, and dividend substitution - Jiang, Zhan; Kim, Kenneth A.; Lie, Erik; Yang, Sean (Journal of Corporate Finance, 2013)
We first extend Baker and Wurgler's (2004a) catering theory of dividends to share repurchases. Consistent with the notion that firms cater to investor demand for share repurchases, we report evidence that the market's time-varying repurchase premium positively affects firms' choice to repurchase shares. Next, we use the catering behavior as a novel framework for testing the dividend substitution hypothesis. Consistent with the notion that managers consider dividends and share repurchases to be substitute payout mechanisms, we find that the dividend premium negatively affects the repurchase choice, whereas the repurchase premium negatively affects the choice to pay dividends.